COMPARING PUBLIC UNIVERSITY LIBRARIES’ SERVICES: EVIDENCES FROM AR-RANIRY ISLAMIC STATE UNIVERSITY AND SYIAH KUALA UNIVERSITY BANDA ACEH - Candra Adi Kurnia; Saiful Akmal; Siti Nur Zalikha; Eka Januar; Radhiyatussuraya (Jurnal Transformasi Administrasi, 2023)
Banda Aceh is the provincial capital of Aceh and has been declared as an economic mobility and education center. This period was marked by the establishment of several public and private schools, as well as public and private universities. Education is a process of learning that aims to develop a generation to be more reliable and capable. Facilities and infrastructure are critical components of education. An essential educational facility for both students and educators is the library. As a public institution, the library must comply with applicable rules and regulations namely UU No. 25 of 2009. The purpose of this study is to establish public services at the UIN Ar-Raniry and USK libraries. This research employs a qualitative approach. The findings indicated that the two libraries were extremely capable of providing services to these public institutions. Numerous supporting aspects contribute to the creation of satisfactory service. Additionally, there are various obstacles to the implementation of public services. Minor errors that occur in each institution are a constant source of progress that must be developed over time. This study concludes that public services provided to UIN Ar-Raniry and USK libraries have begun to show results in compliance with UU No. 25 of 2009. However, further efforts are required on the side of the library's internal and external stakeholders to ensure that the implementation of future services sincerely achieves the law's standardization